2010
DOI: 10.1016/j.ctrv.2010.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Targets for cancer therapy in childhood sarcomas

Abstract: Development of chemotherapeutic treatment modalities resulted in a dramatic increase in the survival of children with many types of cancer. Still, in case of some pediatric cancer entities including rhabdomyosarcoma, osteosarcoma and Ewing's sarcoma, survival of patients remains dismal and novel treatment approaches are urgently needed. Therefore, based on the concept of targeted therapy, numerous potential targets for the treatment of these cancers have been evaluated pre-clinically or in some cases even clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
60
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(60 citation statements)
references
References 176 publications
0
60
0
Order By: Relevance
“…The improvement in survival was closely related to rapid disease recognition and advances in applying surgery, radiotherapy, multi‐drug, multi‐cycle adjuvant chemotherapy regimes 11, 22. However, there was little progress in improving the survival of osteosarcoma in the three decades despite the multi‐modal approach, and treatment is accompanied by many early and late side effects 23, 24. This highlights the urgency of developing novel and more specific therapeutic approaches to improve the outcome of osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement in survival was closely related to rapid disease recognition and advances in applying surgery, radiotherapy, multi‐drug, multi‐cycle adjuvant chemotherapy regimes 11, 22. However, there was little progress in improving the survival of osteosarcoma in the three decades despite the multi‐modal approach, and treatment is accompanied by many early and late side effects 23, 24. This highlights the urgency of developing novel and more specific therapeutic approaches to improve the outcome of osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Relationship between survivin expression and RMS are still unknown. However, some antiapoptotic activities were detected in RMS (38,39). Survivin was strongly overexpressed in both alveolar and embryonal RMS cell lines and in RMS biopsy specimens (40).…”
Section: Discussionmentioning
confidence: 99%
“…129 Currently, the main molecular targets under investigation to improve therapies for advanced, recurrent and metastatic RMS include receptors (IGF-1R, c-Met, PDGFR,c-Kit), intracellular signaling molecules (mTOR, MEK/ERK), cell cycle (CDK4/CDK6) and apoptotic proteins (p53, Bcl-2, TRAIL), the proteasome machinery, HSP90, histone deacetylases, angiogenetic molecules (VEGFR, VEGF), and the Pax3-Foxo1 oncoprotein (all these targets have already been extensively discussed in ref. 130 ). While preclinical in vitro and in vivo studies have suggested the effectiveness of inhibitors targeting RTK like IGF-1R and PDGF-R, 131 and pathways like the AKTmTOR, results from recently published clinical trials have indicated that these therapies are not sufficient to improve the outcome in patients with recurrent disease (Table 1).…”
Section: Targeting Intratumor Cell Heterogeneity: a Difficult But Promentioning
confidence: 99%